Urinary liver-type fatty acid-binding protein levels may be associated with the occurrence of acute kidney injury induced by trauma - Yasuda, Ryu; Suzuki, Keiko; Okada, Hideshi; Ishihara, Takuma; Minamiyama, Toru; Kamidani, Ryo; Kitagawa, Yuichiro; Fukuta, Tetsuya; Suzuki, Kodai; Miyake, Takahito; Yoshida, Shozo; Tetsuka, Nobuyuki; et al. (Frontiers in Medicine, 2024)
Acute kidney injury (AKI), with a fatality rate of 8.6%, is one of the most common types of multiorgan failure in the intensive care unit (ICU). Thus, AKI should be diagnosed early, and early interventions should be implemented. Urinary liver-type fatty acid-binding protein (L-FABP) could aid in the diagnosis of AKI. In this prospective, single-center, observational study, we included 100 patients with trauma. Urinary L-FABP levels were measured using a semi-quantitative rapid assay kit 6 and 12 hours after injury. Negative, weakly positive, and strongly positive urinary L-FABP levels were examined using two protocols. Using protocol 1, measurements were performed at 6 hours after injury negative levels were considered “negative,” and weakly positive and strongly positive levels were considered “positive.” Using protocol 2, strongly positive levels at 6 hours after injury were considered “positive,” and negative or weakly positive levels at 6 hours after injury were considered “positive” if they were weakly positive or positive at 12 hours after injury. Fifteen patients were diagnosed with AKI. Using protocol 1, the odds ratio (OR) was 20.55 (p=0.001) after adjustment for the injury severity score(ISS), contrast media use, and shock index. When the L-FABP levels at 6 and 12 hours were similarly adjusted for those three factors, the OR was 18.24 (p<0.001). The difference in ORs for protocols 1 and 2 was 1.619 (p=0.04). Associations between urinary L-FABP and AKI can be examined more precisely by performing measurements at 6 and 12 hours after injury than only one time at 6 hours.